Nonpharmacological Methods to Reduce Pain During Active Labor in A Real-life Setting - Silva, Clarissa Bernardes de Oliveira; Rodrigues, Karine Mendonça Davi; Zoldan, Camila; Nomura, Roseli Mieko Yamamoto; Araujo Júnior, Edward; Peixoto, Alberto Borges (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2023)
Objective To evaluate the association between pain intensity in the active phase of the first stage of labor with the use or not of nonpharmacological methods for pain relief in a real-life scenario.Methods This was an observational cross-sectional study. The variables analyzed were obtained by a questionnaire with the mothers (up to 48 hours postpartum) to investigate the intensity of pain during labor using the visual analog scale (VAS). The nonpharmacological pain relief methods routinely used in obstetric practice were evaluated by consulting medical records. The patients were separated into two groups: Group I – patients who did not use nonpharmacological methods for pain relief and Group II –patients who used these methods.Results A total of 439 women who underwent vaginal delivery were included; 386 (87.9%) used at least 1 nonpharmacological method and 53 (12.1%) did not. The women who did not use nonpharmacological methods had significantly lower gestational age (37.2 versus 39.6 weeks, p < 0.001) and shorter duration of labor (24 versus 114 min, p < 0.001) than those who used the methods. There was no statistically significant difference in the pain scale score using the VAS between the group that used nonpharmacological methods and the group that did not (median 10 [minimum 2–maximum 10] versus 10 [minimum 6–maximum 10] p = 0.334).Conclusion In a real-life setting, there was no difference in labor pain intensity between the patients who used nonpharmacological methods and those who did not use them during the active phase of labor.
Keywords: labor delivery; pain; intensity; visual analog scale